2004
DOI: 10.1159/000082769
|View full text |Cite
|
Sign up to set email alerts
|

Is Epilepsy Surgery on both Hemispheres Effective?

Abstract: Background: Patients with bilateral independent seizure foci are poor candidates for conventional resective epilepsy surgery. The authors have therefore used minimally invasive procedures to treat such patients. In this paper, the result of a large series of patients treated by this approach is examined to determine the effectiveness of this approach. Materials and Methods: The series had 61 patients. The range of follow-up was 15–90 months. The mean follow-up was 41.5 months with a median of 37 months. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…This is greater than 50% reduction in seizures in 86% of the patients at 2 years follow-up [12]. Similar results were seen in patients who had MST as the primary procedure for extra-temporal onset seizures [1,[3][4][5][6]. Effectiveness of VNS therapy as a primary surgical intervention for intractable epilepsy has been reported in several publications.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This is greater than 50% reduction in seizures in 86% of the patients at 2 years follow-up [12]. Similar results were seen in patients who had MST as the primary procedure for extra-temporal onset seizures [1,[3][4][5][6]. Effectiveness of VNS therapy as a primary surgical intervention for intractable epilepsy has been reported in several publications.…”
Section: Discussionsupporting
confidence: 72%
“…Further-more, the outcome is better than those who had MST alone, resection alone, or VNS therapy alone for extra-temporal onset epilepsy. The result of patients who had MST alone at our center has been described in our previous publications [1,3,4]. In addition, the improvement with VNS therapy after MST as the primary operation is significantly better that those who had VNS therapy following major resective surgery for extra-temporal seizures.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This is a recently developed method for the treatment of epilepsy that reduces the frequency of disabling partial seizures and monitors epileptic discharges long enough to judge the side of the majority of the seizures, therefore enabling the modification of the surgical strategy (5,1618,19). If epileptic activities of either side arise from the temporal neocortex, it is suggested that bipolar coagulation on functional cortices (BCFC) or multiple subpial transection (MST) are combined with selective amygdalohippocampectomy (SAH), respectively, according to the sites of the epileptogenic foci, i.e., in the amygdalohippocampal complex or temporal neocortex (20,21). Furthermore, it is suggested that additional points of view are sought in the treatment of similar cases of epilepsy.…”
Section: Discussionmentioning
confidence: 99%